รัฐธรรมนูญแห่งราชอาณาจักรไทย พ.ศ. 2540 กับ สิทธิและเสรีภาพของนิติบุคคลตามกฎหมายมหาชน - แพรพรรณ ศรีอนันต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This thesis aims to study the rights and liberties of public juristic person under the Constitution of the Kingdom of Thailand B.E. 2540. The study focuses on the acknowledgement of the rights and liberties of individual person and private juristic person under Chapter III "Rights and Liberties of Thai People" of the Constitution of the Kingdom of Thailand B.E. 2540. In addition, the study compares the concepts of the rights and liberties of public juristic person among countries in order to analyze whether and how those concepts impact to the acknowledgement of rights and liberties of Thai public juristic person. The result of the study revels that the public juristic person rights and liberties would be acknowledged by the Constitution of the Kingdom of Thailand B.E. 2540 after the definition of the organization of the Thai public juristic person and the condition of the public juristic person holding some rights and liberties according to Constitution are examined. There are two types of Thai public juristic person which could be rights holder under the Constitution of Kingdom of Thailand B.E. 2540, namely, the State or the organization under the command of the state and the organization under the governance of the State. However, the organization under the command of the State is obliged to acknowledge and protect rights and liberties of other person. The State and organization under the command of the State could not be rights holder under the Constitution of Kingdom of Thailand B.E. 2540. Consequently, only the organization under the governance of the State which is local government organization, State enterprise founded as government agency, public agency, State higher education institutions and the administrative organization of the independent agency under the Constitution could be person holding some rights and liberties under the Constitution of Kingdom of Thailand B.E. 2540.